Solution of drift kinetic equation in stellarators and tokamaks with broken symmetry using the code NEO-2. (31st August 2016) - Kernbichler, W; Kasilov, S V; Kapper, G; Martitsch, A F; Nemov, V V; Albert, C; Heyn, M F
Abstract: NEO-2 is a linearized drift kinetic equation solver for three-dimensional toroidal magnetic fields. It has been designed in order to treat effectively—besides all other regimes—the long mean free path regime, avoiding any simplifications on device geometry or on the Coulomb collision model. The code is based on the field line integration technique combined with a multiple domain decomposition approach, which allows for introduction of an adaptive grid in velocity space. This makes NEO-2 capable of effectively resolving all boundary layers between various classes of trapped particles and passing particles, and also allows for straightforward code parallelization. In stellarators, NEO-2 is used mainly for computations of neoclassical transport coefficients in regimes with slow plasma rotation and for the evaluation of the generalized Spitzer function, which plays the role of a current drive efficiency. In tokamaks with small ideal non-axisymmetric magnetic field perturbations, NEO-2 is used for evaluation of the toroidal torque resulting from these perturbations (neoclassical toroidal viscosity). The limitation to slow plasma rotation pertinent to usage in stellarators has been removed in this case with the help of a quasilinear approach, which is valid due to the smallness of the perturbation field.